THE TAXONOMIC STATUS OF PTERYGODERMATITES SPP. AND THE SCANNING ELECTRONMICROSCOPY STUDY OF PTERYGODERMATITES WHARTONI (TUBANGUI, 1931) (NEMATODA: RICTULARIIDAE) FROM INDONESIAN MURIDS - Kartika Dewi (Masyarakat Zoologi Indonesia, 2010)
Species